Influence of exposure time to coffee on color stability of selected composite resin veneers/ Amar M Thiyab, Nik Zarina N Mahmood and Mohamed Ibrahim A Hassan - Thiyab, Amar M; N Mahmood, Nik Zarina; A Hassan, Mohamed Ibrahim (Faculty of Dentistry, 2016)
The aim of the study is to evaluate the effect of the time and instant coffee solution on the color stability of three types of composite resin based veneer systems. 24 composite resin veneer samples were selected and divided into three groups: two groups of prefabricated veneers (Edelweiss, Ultradent Inc™ (EDL) and Componeer, Coltène/Whaledent AGTM (CMP)) and one group of laboratory made (Nexco, Ivoclar Vivadent (NEX)) veneer system were tested (n=8). Specimens were prepared and stored in staining solution (instant coffee) and assessed color changes with Minolta spectrophotometer every three days for a period of 27 days, after which color differences (ΔE*) were calculated. Data collection and analysis was done using one-way ANOVA and Student’s t-test (α=0.05). One-way ANOVA revealed a significant difference in color stability between the two veneer systems. NEX group veneer system exhibited the highest color stability (ΔE*= 0.73 ± 0.5) as compared to prefabricated veneer groups (EDL 10.07 ± 5.15, CMP 7.41 ± 4.64) with p value <0.05. The color stability (ΔE*) of the laboratory made veneer system is significantly higher than the prefabricated veneer systems and more clinically accepted.